ROLE OF LOCAL HYPERTHERMIA IN COMBINED MODALITY TREATMENT OF SOFT TISSUE SARCOMAS - Zh. A. Startseva; Е. М. Slonimskaya; Yu. I. Tyukalov; I. G. Frolova; A. A. Zheravin; A. I. Konovalov; К. A. Simonov; А. V. Bogoutdinova; О. V. Kotova (Сибирский онкологический журнал)
The review aimed to assess the role of local hyperthermia in combined modality treatment of soft tissue sarcoma. The recent randomized trials have shown significant benefits from local hyperthermia in patients with soft tissue sarcoma. When combined with radiotherapy, hyperthermia has a complementary and additive effect. Extensive researches have also shown that hyperthermia improves the efficacy of many chemotherapeutic agents. Besides the increased effectiveness of radiotherapy and chemotherapy, hyperthermia has many anti-cancer effects and improves treatment results in patients with soft tissue sarcomas.